Log-periodic quantum magneto-oscillations and discrete-scale invariance in topological material HfTe5. Issue 5 (6th August 2019) - Wang, Huichao; Liu, Yanzhao; Liu, Yongjie; Xi, Chuanying; Wang, Junfeng; Liu, Jun; Wang, Yong; Li, Liang; Lau, Shu Ping; Tian, Mingliang; Yan, Jiaqiang; Mandrus, David; et al.
Abstract: Discrete-scale invariance (DSI) is a phenomenon featuring intriguing log-periodicity that can be rarely observed in quantum systems. Here, we report the log-periodic quantum oscillations in the longitudinal magnetoresistivity ( ρxx ) and the Hall traces ( ρyx ) of HfTe5 crystals, which reveal the DSI in the transport-coefficients matrix. The oscillations in ρxx and ρyx show the consistent log B -periodicity with a phase shift. The finding of the log B oscillations in the Hall resistance supports the physical mechanism as a general quantum effect originating from the resonant scattering. Combined with theoretical simulations, we further clarify the origin of the log-periodic oscillations and the DSI in the topological materials. This work evidences the universality of the DSI in the Dirac materials and provides indispensable information for a full understanding of this novel phenomenon.